Yield, Esterification Degree and Molecular Weight Evaluation of Pectins Isolated from Orange and Grapefruit Peels under Different Conditions. - Mohamed Yassine Sayah; Rachida Chabir; Hamid Benyahia; Youssef Rodi Kandri; Fouad Ouazzani Chahdi; Hanan Touzani; Faouzi Errachidi (PLoS ONE, 2016)
Orange (Citrus sinensis) and grapefruit (Citrus paradise) peels were used as a source of pectin, which was extracted under different conditions. The peels are used under two states: fresh and residual (after essential oil extraction). Organic acid (citric acid) and mineral acid (sulfuric acid) were used in the pectin extraction. The aim of this study is the evaluation the effect of extraction conditions on pectin yield, degree of esterification "DE" and on molecular weight "Mw". Results showed that the pectin yield was higher using the residual peels. Moreover, both peels allow the obtainment of a high methoxyl pectin with DE >50%. The molecular weight was calculated using Mark-Houwink-Sakurada equation which describes its relationship with intrinsic viscosity. This later was determined using four equations; Huggins equation, kramer, Schulz-Blaschke and Martin equation. The molecular weight varied from 1.538 x1005 to 2.47x1005 g/mol for grapefruit pectin and from 1.639 x1005 to 2.471 x1005 g/mol for orange pectin.